Dinamika Pelestarian Tradisi Maulid Diba’ oleh Kader Pemuda NU: Antara Ketahanan Budaya dan Adaptasi di Era Society 5.0 - Ferdianto, Achmad Nur; Fahmi, Ahmad Rosikhul; Hilmi, Annafik Fuad; Syafiq, Muhammad Khoirul; Hasan, Raihan Malikal; As-Sya'ban, Muhammad Rizqy Kamaluddin (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2025)
This study examines the dynamics of preserving the Maulid Diba' tradition by young cadres of Nahdlatul Ulama (IPNU-IPPNU) in Tasikmadu, focusing on the balance between cultural resilience and adaptation in the era of Society 5.0. The research method uses a mixed method approach involving quantitative surveys and qualitative interviews with IPNU-IPPNU members. The results of the study indicate that cadres have a deep understanding and active participation in the implementation of Maulid Diba', which acts as a medium for religious education as well as strengthening social solidarity. However, there are challenges in terms of innovation and organizational coordination to maintain the relevance of tradition amidst technological developments and social change. This study emphasizes the strategic role of IPNU-IPPNU in preserving religious traditions while adapting to the demands of the times, so that the Maulid Diba' tradition remains alive and meaningful for the younger generation. Recommendations are given for strengthening organizational capacity, innovation in implementation methods, and utilization of digital technology.